Involvement of protein sulfhydryls in the trigger reaction of rhodotorucine A, a farnesyl peptide mating pheromone of Rhodosporidium toruloides. - Miyakawa, T (1985)
The involvement of protein sulfhydryls for the signaling of rhodotorucine A, a mating pheromone produced by mating type A cells of Rhodosporidium toruloides, was investigated by the use of sulfhydryl compounds. The sulfhydryl-blocking reagent 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB; Ellman's reagent) strongly inhibited both the biological effect of the pheromone on the recipient cell and the hydrolysis of the pheromone, which is catalyzed by the mating type-specific surface endopeptidase of the recipient cell. Conversely, the two reactions were markedly enhanced by the presence of the reducing reagent dithiothreitol. The inhibitory effect of DTNB on the pheromone response of the recipient cell was specific to an initial stage of the differentiation; once it had initiated, the reagent had no effect on its progression. The results suggested that dithiothreitol enhances and DTNB impairs the efficiency with which the pheromone triggers sexual d differentiation. The reaction of DTNB with cellular protein sulfhydryls was highly restricted to those at the exterior surface of the membrane due to the impermeability of the reagent through the membrane. Phosphorylation of endogenous proteins, which is modulated by the pheromone added to an in vitro phosphorylation system, was also blocked by DTNB. The results showed that sulfhydryl groups are involved in the pheromone hydrolysis by the surface endopeptidase of the recipient cell and that pheromone metabolism is indispensable for the signaling reaction. We suggest that the modulation of protein phosphorylation of membrane proteins by the pheromone is an initial transmembrane response coupled to pheromone metabolism.